Efficient Plant Regeneration from Shoot Apices of Pearl Millet (Pennisetum americanum (L.) Leeke) - Varalaxmi, Y.; Vijayalakshmi, A.; Kumar, K. Ravi; Vijayalakshmi, T.; Maheswari, M. (Plant Tissue Culture and Biotechnology, 2010)
An efficient and rapid regeneration protocol was developed from shoot tip explants of Pennisetum americanum (L.) Leeke variety WC-75. MS supplemented with low concentration of 2,4-D and Kn was most effective in producing embryogenic calli. Maximum regeneration potential of 40 shoots per calli were obtained when transferred to regeneration medium containing 1.0 mg/l Kn. Shoots developed were efficiently rooted within 15 days on the medium containing NAA. Over 90% of rooted plants were fertile after transfer to a net house. Key words: Pearl millet, Efficient, plant regeneration, Shoot apices D.O.I. 10.3329/ptcb.v20i1.5964 Plant Tissue Cult. & Biotech. 20(1): 47-53, 2010 (June)